Corporate Financial Strategy in the Energy Transition: Investment, Risk, and Policy Frameworks - Chukwukaelo, Uche (New Advances in Business, Management and Economics Vol. 6, 2025)
Corporate finance strategies play an important part in this transformation, providing a link between existing energy practices and a more sustainable future. The shift toward sustainable energy requires a significant transformation in corporate financial strategies, particularly in the allocation of capital for renewable energy projects. The aim of this study is to explore the critical financial considerations influencing the transition, including investment mechanisms, the cost of capital, and risk mitigation strategies. Green bonds and sustainability-linked loans are two crucial factors that corporations in the energy sector increasingly rely on to raise capital for renewable energy projects. These instruments offer financial incentives for organisations to meet sustainability targets, lowering borrowing costs and ultimately enhancing corporate ESG (Environmental, Social, and Governance) performance. Many corporations have been known for entering joint ventures and strategic partnerships by which they share financial risks and leverage complementary expertise. By leveraging these adaptive financial approaches, corporations are able to better navigate the evolving energy landscape and ensure long-term sustainability.